Prevalence of Amblyopia in children in Karachi, Pakistan ? A Hospital based study - Mazhar-ul-Hasan, Saba Alkahiry, Farnaz Siddiqui (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the prevalence and causes of Amblyopia amongst children presenting to the OPD department of Dow University of Health Science, Dow International Medical College, Karachi, Pakistan. Study Design: Cross sectional study Place and Duration of Study: Eye OPD of Dow University of Health Science (ohja campus), Karachi, Pakistan from January 2016 to June 2016. Material and Methods: This was a cross sectional study conducted in the eye OPD of Dow University of Health Science, Karachi, Pakistan. All children aged 5 to 20 years were examined. They underwent Visual Acuity assessment with Snellen acuity chart. Those with visual acuity less than or equal to 6l9 or with them having a bilateral difference of two visual acuity lines on Snellens Chart were examined further with cycloplegic refraction with tropicamide 1% and dilated fundoscopy. Further tests included Hirschberg light reflex test, cover uncover test, prism cover-uncover and extraocular movements. Results: A total of 2500 children were screened and 169 (6.7%) were found to be amblyopic. There were 61 (36.1%) amblyopic males and 108 (63.9%) amblyopic females. Amblyopia was most commonly seen in the age group less than 12 years 63 (37.3%) and the most common cause of amblyopia was isometropia 61 (36.1%) followed by meridional 45 (36.6% mixed 42 (24.9%), anisometropia 15 (8.8%) and squint 6 (3.6%). Conclusion: The prevalence of amblyopia among children presenting to the OPD of Dow University of Health Science is determined to be 6.7% which is higher than any other published studies on amblyopia. Key Words: Amblyopia, Screening, Strabismus